John Louk ’s Political Thought and Political Philosophy - فلاح حسن آسارى (Al-Adab Journal, 2018)
political thought is Interested in organized in life, existing in a society, in all its aspects, while the political philosophy is expressive of personality that will take, and reflect the experiences lived during the period of his life. Political philosophy may address political thought, and the most important themes is the authority. Throughout history, appeared several intellectuals, take the development of political thought, including philosopher Jean-Marc Locke (1632 1704), is philosopher in modern philosophy and in individual liberal, and Representative of the doctrine of perception, and a supporter of freedom, and interested in the theory of knowledge, and is interested in the problems of society and the state, and his work affected in the development of philosophical and political thought of modern and contemporary, especially in individual freedom. The highlight of taking John Locke is the theory of separation of powers, and established the idea of ​​tolerance, and the idea of ​​a civil state, as well as the social contract theory of the evolution of the state.